2017
DOI: 10.5565/rev/catjl.212
|View full text |Cite
|
Sign up to set email alerts
|

Late Latin Verb Second: The Sentential Word Order of the “Itinerarium Egeriae”

Abstract: In this article we undertake a systematic study of the Itinerarium Egeriae, one of the best known late Latin texts, to determine the proper characterization of the word order of the text and to consider in particular whether the Itinerarium Egeriae can legitimately be considered to present a verb-second (V2) grammar on the par with the well-studied grammars of medieval Romance. The results, based on detailed quantitative and qualitative analyses of the text and, where relevant, appropriate comparisons with med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Como tienen un 21 La cita de Lapesa (1981, p. 112) soporta la propuesta que hago: "Los germanos, enseñoreados del territorio romano, conservaban con plena vitalidad sus lenguas, y los latinos aprendían de ellos denominaciones de cosas y costumbres extrañas, familiarizándose con expresiones germánicas". Ledgeway (2017) argumenta consistentemente que el latín tardío ya manifestaba la propiedad V2. 22 No he logrado comprender si los francos hablaban francés o alguna lengua germánica.…”
Section: Consideraciones Finalesunclassified
“…Como tienen un 21 La cita de Lapesa (1981, p. 112) soporta la propuesta que hago: "Los germanos, enseñoreados del territorio romano, conservaban con plena vitalidad sus lenguas, y los latinos aprendían de ellos denominaciones de cosas y costumbres extrañas, familiarizándose con expresiones germánicas". Ledgeway (2017) argumenta consistentemente que el latín tardío ya manifestaba la propiedad V2. 22 No he logrado comprender si los francos hablaban francés o alguna lengua germánica.…”
Section: Consideraciones Finalesunclassified
“…A first observation is that SI does not occur in clause-medial or final position, and it must thus be analysed as a CP-element. Based on data from Ledgeway (2017), Wolfe (2018) shows that SI could occur clause-medially in Late Latin. By Early Old French, he assumes that SI is base generated in the High Adverb field and obligatorily moved to SpecFinP.…”
Section: A Structural Analysis Of Old Frenchmentioning
confidence: 99%
“…The origin of this structure has also been debated. While it has been suggested that V2 in the Romance languages is the result of language contact with Germanic languages (Mathieu, 2007a,b), this view has been challenged and it has been suggested that V2 evolves independently in these languages (Wolfe, 2015a(Wolfe, ,b, 2019Ledgeway, 2017;Klaevik-Pettersen, 2018).…”
Section: Old Romancementioning
confidence: 99%
“…However, the presence of V o -to-C o movement, systematic subject inversion and main-embedded asymmetries are indications of a structural V2 word order. Strictly speaking, V o -to-C o movement is in itself taken as the definition of V2 by a number of scholars (Benincà, 2006;Wolfe, 2015bWolfe, , 2019Ledgeway, 2017).…”
Section: V2 Violationsmentioning
confidence: 99%